Decadência de Portugal e o Cesarismo : um estudo sobre a historiografia de J. P. de Oliveira Martins - Botton, Rafael Reigada (2016)
This dissertation consists of an analysis about Joaquim Pedro de Oliveira Martins’s historiography, focusing over his conceptions about the decay of the Portuguese nation; and about the historiographical constructions related to de Caesarism concept. It will be also analyzed the politic and cultural contexts of development of the Generation of 1870, and how the ideia of decay articulated the cohesion between its members (focusing on its theorist theoretical foundation on Oliveira Martins’s thought, specially, the Hegel’s dialectic logic and the theories about social organicism). It will be used as research methodology the historical categories of Space of Experience and Horizon of Expectation of Reinhart Koselleck, intending to constitute a historical hermeneutic adequate to study the analogies established between the historical circles of Portugal’s history, and its relation with the Roman Republic. It will be also analysed the main postulates of the cathedratic socialism, and its influence over Oliveira Martins’s political thought, also reflecting on his historiography. It’s intended to problematize the borders between historical production and political thought, as much about the readings of Portuguese history that provided multiple interpretations about the Portuguese national identity.